Uganda : 2008 Article IV Consultation and Fourth Review Under the Policy Support Instrument; Staff Report; Staff Supplement; Public Information Notice and Press Release on the Executive Board Discussion; and Statement by the Executive Director for Uganda. (IMF Staff Country Reports; Country Report, 2009)
The staff report for Uganda's combined 2008 Article IV Consultation and Fourth Review Under the Policy Support Instrument is presented. Building on a foundation of two decades of sound policies, Uganda achieved an impressive economic performance, with high growth, low inflation, and steady poverty reduction. The deteriorating economic environment could expose weaknesses in banks' risk management practices, gaps in home-host supervisory arrangements, operational risks as financial innovation outpaces banks' systems and controls, and increasing risk appetite owing to intensifying competition from the surge of new banks.